Biodegradable scaffold with nano-materials for treating heart disease - Toong, Daniel Wee Yee (Nanyang Technological University, 2022)
The development of bioresorbable scaffolds/stents (BRS) has been termed as the 4th revolution in interventional cardiology. The current poly-L-lactic acid (PLLA) BRS have thick stents struts to provide radial support for the artery but led to issues like stent thrombosis, which requires extended periods of dual anti-platelet therapy. Hence, the motivation of this thesis is to reduce stent strut thickness with the use of nanocomposite materials by enhancing their mechanical properties (primarily Young’s modulus) of PLLA. The addition of functionalised radiopaque nanofillers is anticipated to impart mechanical strength and confer radiopacity to the polymer matrix, translating to thinner stent struts. This could potentially reduce the risk of stent thrombosis, promote endothelialisation and positive remodelling of the vessel. The initial research of the thesis aims to evaluate the properties material formulation and their properties. Eight groups of materials (PLLA, BaSO4/PLLA, stearic acid functionalised (SA)-BaSO4/PLLA, lactide oligomers functionalised (LA)-BaSO4/PLLA, Ta2O5/PLLA, LA-Ta2O5/PLLA, hydroxyapatite (HA)/PLLA and LA-HA/PLLA) were fabricated with different loading concentrations using melt blending and extruded into fibres. The addition of nanofillers to the PLLA matrix generally improved the mechanical properties before declining due to effects of agglomeration. 15% BaSO4/PLLA, 15% Ta2O5 and 5% HA at their optimal loading have improved their tensile modulus by 21.2%, 48.8% and 67.6% from PLLA respectively. On the other hand, 15% SA-BaSO4/PLLA, 15% LA-BaSO4/PLLA, 15% LA-Ta2O5/PLLA and 10% LA-HA/PLLA at their optimal loading, have improvement of tensile modulus of 13.5%, 103%, 75.9% and 69.4% from PLLA respectively. Functionalisation of nanofillers has also helped to improve ductility in PLLA as compared to non-functionalised nanofillers. TEM images revealed that functionalisation of the nanofillers generally helps to improve dispersion of nanofillers in PLLA matrix, mitigating the effect of stress concentration and could facilitate a more effective stress transfer from the matrix to the reinforcement phase. The introduction of BaSO4 and Ta2O5 nanofillers at a low loading can also impart radiopacity to the PLLA matrix. The strengthening mechanism of nanocomposites are then subsequently predicted and evaluated by utilising several composite models. Various parameters such as agglomeration parameter from Yasser model and stress concentration parameter from Kunori-Geil model have a correlation that validates the mechanical behaviour of nanocomposite. Non-functionalised nanofillers/PLLA tend to exhibit a higher agglomeration factor than functionalised nanofillers/PLLA, explaining the purpose of the functional groups on the surface of the nanofillers, that is to promote dispersion within the matrix. The interaction parameter proposed by Pukanszky and Sato-Furukawa, has also validated the nanofiller-matrix interaction of the functionalisation nanofillers/PLLA to be more superior to the non-functionalised nanofillers/PLLA. LA functionalised nanofillers exhibited more compatibility as they have similar chemical repeating groups to PLLA, therefore similar hydrophilicity. The adhesion parameter also implies the effective stress transfer from matrix to filler, resulting in enhanced Young’s modulus and strength. The evaluation of the stent model (bioresorbable vascular scaffold) with material properties obtained was conducted via computational simulation. Stents struts width and thickness of 80, 100 and 150 μm of different permutations were evaluated for the performance in terms of deployment and radial properties. The stent width of 150 μm acts as a strong anchor point regardless of material to achieve high radial strength and material to undergo yielding when subjected to deployment. The optimal loading of material formulation of LA-Ta2O5/PLLA and LA-HA/PLLA are able to provide an equal or higher radial strength to PLLA when stent strut thickness is being reduced from 150 μm to 80 μm. The stent made of the materials are also well within the limits of stent fracture. In conclusion, functionalised nanofillers can help improve mechanical behaviour, and radiopacity of PLLA, and the use of nanocomposite materials are able to reduce stent profile significantly.